PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. GLOBAL INFORMASI BERMUTU KEBON JERUK JAKARTA BARAT - Noto Susanto; N Lilis Suryani; Iman Syatoto; Darmadi Darmadi (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The purpose of this study is to determine the influence of leadership on employee performance, the effect of motivation on employee performance and leadership and motivation simultaneously on employee performance at PT. Global Quality Information. This research uses quantitative research with sampling using simple random sampling technique. Based on the analysis that has been done, there is a significant influence of leadership on employee performance with a regression coefficient of 0.127. There is a significant effect of motivation on employee performance with a regression coefficient of 0.682. There is a significant influence of leadership and motivation on performance with a contribution of 47.2%. This finding firmly confirms the fact that at work, it is very necessary to have a good leader who is able to bring positive changes to employees and the company. In addition, the existence of self-motivation or the desire to work with enthusiasm is a factor that also determines how productivity and performance increase.